2003
DOI: 10.1002/gps.864
|View full text |Cite
|
Sign up to set email alerts
|

Delusions of Japanese patients with Alzheimer's disease

Abstract: The authors found a high frequency of delusions, particularly of delusions of theft and suggested that gender was associated with the expression of delusions in Japanese patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 42 publications
2
54
1
1
Order By: Relevance
“…However, the mechanism for delusions in AD patients is not well understood. Some studies which did not use an age limit reported that being female is linked to delusions in AD Launer et al, 1999;Ikeda et al, 2003). Therefore, there is a possibility that our results were strongly influenced by sex ratio.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the mechanism for delusions in AD patients is not well understood. Some studies which did not use an age limit reported that being female is linked to delusions in AD Launer et al, 1999;Ikeda et al, 2003). Therefore, there is a possibility that our results were strongly influenced by sex ratio.…”
Section: Discussioncontrasting
confidence: 52%
“…Female predominance in delusion was also evident in this study. The discrepancy between Western countries and Japan may be attributed to methodological and sociocultural differences, as suggested by Ikeda et al [6] .…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of delusions was reported as 22% by Mega et al [20] , 46.7% by Ozawa [21] , 38.6% by Hirono et al [22] , 55% by Wilson et al [23] , and 47.3% by Ikeda et al [6] . In this study, 39.1% of the AD patients exhibited delusions, with this fi gure well within the range reported in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…알츠하이머병 환자에서 망상의 유병률은 10-73%로 보고되고 있 으며 [17], 최근 연구에서는 알츠하이머병 환자의 약 삼분의 일에서 망 상이 있다고 보고되었다 [17][18][19][20]. 따라서 환경적인 조절이 중요하다 [73].…”
Section: 유병률unclassified